High-sulfur coke-based fast-charge artificial graphite negative electrode material as well as preparation method and application thereof
By mixing high sulfur coke with modified asphalt for carbonization and graphitization, a fast-charge artificial graphite negative electrode material with secondary particle structure and nanopores was prepared, which solved the problem of low rate performance in the prior art and achieved efficient lithium ion diffusion and electrochemical performance improvement.
Patent Information
- Application Number
- CN202411818665.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The current lithium-ion battery negative electrode materials have low rate performance, which is difficult to meet the demand for fast charging and discharge. The structure converted from the binder during graphitization is dense, reducing the diffusion rate of lithium ions.
By heat-treated high-sulfur coke and mixed with modified asphalt, carbonization and graphitization are performed, a fast-charge artificial graphite negative electrode material with secondary particle structure and nanopores were prepared. The method includes a heat treatment process of segmented heating to remove sulfur and to form nanopores during graphitization using metal oxides in modified asphalt.
The rate performance, cycle stability, first-time Coulomb efficiency and charge and discharge capacity of the negative electrode material of lithium-ion battery is significantly improved, and the process is simple, the cost is low, and the raw materials are widely sourced.
Smart Images

Figure BDA0005182536510000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for lithium-ion batteries, and specifically relates to a high-sulfur coke-based fast-charging artificial graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries achieve charge transfer and charging and discharging by the continuous shuttling of lithium ions between the positive and negative electrodes. They are mainly assembled through a series of components such as positive and negative electrodes, separators, and electrolytes. Kinetic performance is a very important performance of positive and negative electrodes, which mainly refers to the ability of lithium ions to quickly embed and extract to achieve rapid charging and discharging of the battery.
[0003] At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite. Graphite is a layered structure material. Carbon atoms in the same layer form relatively strong covalent bonds by sp2 hybridization, and the layers are bonded by van der Waals forces. Because the bonding force between layers is small and the interlayer spacing is large, lithium ions can be embedded and removed, so graphite is an important negative electrode material for lithium-ion batteries and other ion-embedded electrode active materials.
[0004] In practical applications, graphite needs to maintain its intrinsic layered structure and have a relatively large micron-sized particle size, which inevitably leads to slow diffusion kinetics of ion embedding and extraction between graphite layers, and thus the rate performance of graphite negative electrode is low. If pores can be formed in the direction perpendicular to the plane layer of graphite (i.e., C-axis pore formation), the diffusion kinetics can be improved through the diffusion channel in the C-axis direction, but such C-axis pore formation is very difficult.
[0005] Compared with natural graphite, artificial graphite has better dynamic properties. Artificial graphite is generally prepared by graphitizing needle coke or petroleum coke. Petroleum coke is the final byproduct of the delayed coking process in oil refineries. According to the sulfur content, it can be divided into high-sulfur coke (sulfur content greater than 3%), medium-sulfur coke and low-sulfur coke (sulfur content less than 0.5%). The prior art has reported that small particles of high-sulfur coke are mixed with a binder (asphalt or resin) - granulation - desulfurization - graphitization to prepare an artificial graphite negative electrode material with a secondary particle structure (small particles bonded together), and desulfurization is used to achieve C-axis pore formation between graphite layers to improve the rate performance of artificial graphite. However, the graphite or hard carbon converted from asphalt or resin during graphitization has a dense structure, which reduces the diffusion rate of Li+ to the surface of graphite (C-axis pore formation); therefore, this C-axis pore formation method can only improve its rate performance to a certain extent. Therefore, there is an urgent need for a method for preparing artificial graphite with excellent dynamic properties using high-sulfur coke. Summary of the invention
[0006] In order to effectively utilize high-sulfur coke to prepare artificial graphite with excellent kinetic performance, the present invention provides a high-sulfur coke-based fast-charging artificial graphite negative electrode material and a preparation method and application thereof. The fast-charging artificial graphite negative electrode material has the characteristics of high rate performance, good cycle stability, high first coulombic efficiency and large first charge and discharge capacity. The preparation method has the characteristics of simple process, low preparation cost and wide source of raw materials.
[0007] The object of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a fast-charging artificial graphite negative electrode material, the method comprising the following steps:
[0009] (1) heat treating high-sulfur coke to prepare desulfurized coke;
[0010] (2) crushing, shaping and classifying the desulfurized coke obtained in step (1) to obtain desulfurized coke powder;
[0011] (3) mixing asphalt and metal chloride, reacting, and preparing modified asphalt;
[0012] (4) mixing the desulfurized coke powder of step (2) and the modified asphalt of step (3) to react;
[0013] (5) carbonizing the reaction product of step (4) to prepare secondary coke particles;
[0014] (6) graphitizing the secondary coke particles of step (5) to prepare the fast-charging artificial graphite negative electrode material;
[0015] Wherein, in step (1), the heat treatment adopts a staged heating process, which specifically includes the following steps:
[0016] First, heat up to 300-500°C at a heating rate of 10-20°C / min and keep warm for 1-3 hours; then heat up to 800-1200°C at a heating rate of 5-10°C / min and keep warm for 1-3 hours; finally, heat up to 1700-2000°C at a heating rate of 1-5°C / min and keep warm for 1-6 hours.
[0017] According to an embodiment of the present invention, in step (1), the high-sulfur coke is a by-product obtained by treating residual oil in a crude oil refining process through a coking process, and can be purchased through commercial channels.
[0018] According to an embodiment of the present invention, in step (1), the particle size of the high-sulfur coke is not particularly defined, and may be a conventional particle size in the art, such as millimeter-level or centimeter-level high-sulfur coke.
[0019] According to an embodiment of the present invention, in step (1), the sulfur content in the high-sulfur coke is 3-8wt%, for example, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 7wt% or 8wt%. Studies have found that when high-sulfur coke with a sulfur content of 3-8wt% is selected and further combined with the preparation method of the present invention, the C-axis pore formation of graphite and the construction of pores, sites and transmission pathways adapted to lithium ions can be effectively achieved, which helps to obtain an artificial graphite negative electrode material with excellent fast charging performance and other electrochemical properties (such as cycle performance, coulombic efficiency and charge and discharge capacity). When high-sulfur coke with a sulfur content of >8wt% is selected, due to the high sulfur content, the high-sulfur coke structure will easily collapse during the desulfurization process, and the lithium ion transmission channel cannot be effectively formed, so an artificial graphite negative electrode material with high rate performance cannot be obtained; when medium-sulfur coke or low-sulfur coke with a sulfur content of <3wt% is selected, due to the low sulfur content, sulfur volatilization cannot be used to form C-axis pores inside the medium-sulfur coke or low-sulfur coke to construct lithium ion-compatible pores, sites and transmission pathways, and similarly an artificial graphite negative electrode material with high rate performance cannot be obtained.
[0020] According to an embodiment of the present invention, in step (1), the heat treatment is carried out by a staged heating process, specifically comprising heating to 300-500°C (such as 300°C, 350°C, 400°C, 450°C or 500°C) at a heating rate of 10-20°C / min (such as 10°C / min, 12°C / min, 15°C / min, 18°C / min or 20°C / min), keeping the temperature for 1-3 hours (such as 1 hour, 2 hours or 3 hours); then heating to 800-1200°C at a heating rate of 5-10°C / min (such as 5°C / min, 6°C / min, 8°C / min or 10°C / min). ℃ (such as 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃ or 1200℃), and keep it warm for 1-3 hours (such as 1 hour, 2 hours or 3 hours); finally, heat it to 1700-2000℃ (such as 1750℃, 1800℃, 1850℃, 1900℃, 1950℃ or 2000℃) at a heating rate of 1-5℃ / min (such as 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min or 5℃ / min), and keep it warm for 1-6 hours (such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours). Research has found that by adopting the staged heating process of the present invention, it is possible to effectively remove sulfur from high-sulfur coke and achieve C-axis pore formation of graphite. At the same time, it can also effectively prevent the collapse of the high-sulfur coke structure due to the rapid volatilization of sulfur during the heat treatment process, and the inability to construct microporous structures and active sites suitable for the embedding, de-embedding and storage of lithium ions.
[0021] According to an embodiment of the present invention, in step (1), the heat treatment is performed under a nitrogen protective atmosphere.
[0022] According to an embodiment of the present invention, in step (1), the sulfur content in the desulfurized coke is less than 100 ppm.
[0023] According to an embodiment of the present invention, in step (2), the equipment used for the pulverization is not particularly limited, and equipment known in the art can be selected, such as an impact pulverizer, a jet mill, a high-pressure mill or a rod-type mechanical pulverizer.
[0024] According to an embodiment of the present invention, in step (2), the equipment used for the shaping is not particularly limited, and equipment known in the art, such as a mechanical shaping machine or an airflow shaping machine, can be selected.
[0025] According to an embodiment of the present invention, in step (2), the equipment used for the classification is not particularly limited, and equipment known in the art, such as an air flow classifier, can be selected.
[0026] According to an embodiment of the present invention, in step (2), the median particle size D of the desulfurized coke powder is 50 5-8 μm, for example, 5 μm, 6 μm, 7 μm or 8 μm.
[0027] According to an embodiment of the present invention, in step (3), the softening point of the asphalt is 65-75°C, for example, 65°C, 70°C or 75°C.
[0028] According to an embodiment of the present invention, in step (3), the water content in the asphalt is 2-3wt%, for example, 2wt%, 2.2wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.8wt% or 3wt%.
[0029] According to an embodiment of the present invention, in step (3), the metal chloride is selected from AlCl 3 、SiCl 4 or TiCl 4 .
[0030] According to an embodiment of the present invention, in step (3), the mass ratio of the metal chloride to the asphalt is (5-15):100, for example, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100 or 15:100.
[0031] According to an embodiment of the present invention, in step (3), the reaction is carried out under stirring conditions.
[0032] According to an embodiment of the present invention, in step (3), the softening point of the modified asphalt is 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0033] According to an embodiment of the present invention, step (3) specifically includes the following steps:
[0034] Put asphalt into a reactor and heat it to 120-160°C, add metal chloride to the molten asphalt under stirring, react for 0.5-1 hour, then introduce argon into the reactor, continue heating to 330-390°C under argon protection, keep warm for 2-6 hours, and prepare modified asphalt.
[0035] For example, the asphalt is placed in a reactor and heated to 120° C., 130° C., 140° C., 150° C. or 160° C. Reacting at this temperature for 0.5-1 hour can increase the softening point of the asphalt, which is conducive to obtaining a carbonized product with a high carbon residue value after carbonization and ensuring close bonding between the primary particles.
[0036] Illustratively, the heating is continued to 330° C., 340° C., 350° C., 360° C., 370° C., 380° C. or 390° C. under argon protection.
[0037] According to an embodiment of the present invention, in step (3), during the reaction, the metal chloride reacts with the water in the asphalt to generate nano-sized metal oxides (such as Al 2 O 3 、SiO 2 or TiO 2 ), and the generated nano-oxides are evenly distributed in the asphalt to prepare modified asphalt. Compared with the method of directly adding nano-metal oxides to asphalt to obtain modified asphalt, the method of in-situ synthesis of nano-sized metal oxides of the present invention can make the metal oxides evenly distributed in the asphalt. These nano-sized metal oxides can form evenly distributed nanopores after volatilization during the graphitization process. The presence of these nanopores can increase the diffusion channels of lithium ions and improve the rate performance of artificial graphite negative electrode materials; at the same time, the method of in-situ synthesis of nano-sized metal oxides of the present invention can also avoid the formation of macropores inside the artificial graphite negative electrode material during the graphitization process due to uneven dispersion of metal oxides (such as agglomeration), reduce the diffusion channels of lithium ions, and thus fail to effectively improve the rate performance of the negative electrode material.
[0038] According to an embodiment of the present invention, in step (4), the mass ratio of the modified asphalt to the desulfurized coke powder is (8-15):100, for example, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100 or 15:100.
[0039] According to an embodiment of the present invention, in step (4), the reaction temperature is 450-650°C, for example, 450°C, 500°C, 550°C, 600°C or 650°C; the reaction time is 3-12 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours or 12 hours.
[0040] According to an embodiment of the present invention, in step (4), the reaction is carried out under air atmosphere.
[0041] According to an embodiment of the present invention, in step (4), the reaction is naturally cooled to room temperature after completion.
[0042] According to an embodiment of the present invention, in step (4), the reaction is carried out in a granulation kettle.
[0043] According to an embodiment of the present invention, in step (4), during the reaction, the modified asphalt can bond small particles of desulfurized coke powder into a secondary particle structure, which is beneficial for obtaining an artificial graphite negative electrode material with a secondary particle structure.
[0044] According to an embodiment of the present invention, in step (5), the temperature of the carbonization treatment is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C; the time of the carbonization treatment is 3-12 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours or 12 hours.
[0045] According to an embodiment of the present invention, in step (5), during the carbonization process, the pitch is transformed into amorphous carbon.
[0046] According to an embodiment of the present invention, in step (5), the carbonization treatment is naturally cooled to room temperature after completion.
[0047] According to an embodiment of the present invention, in step (5), the carbonization treatment is performed under a nitrogen atmosphere.
[0048] According to an embodiment of the present invention, in step (5), the median particle size D of the secondary coke particles is 50 It is 10-15μm, for example, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.
[0049] According to an embodiment of the present invention, in step (6), the temperature of the graphitization treatment is 2850-3200°C, for example, 2850°C, 2900°C, 2950°C, 3000°C, 3050°C, 3100°C, 3150°C or 3200°C; the time of the graphitization treatment is 8-24 hours, for example, 8 hours, 10 hours, 12 hours, 14 hours, 15 hours, 16 hours, 18 hours, 20 hours or 24 hours.
[0050] According to an embodiment of the present invention, in step (6), during the graphitization process, the metal oxide (Al 2 O 3 、SiO 2 or TiO 2 ) will volatilize from the matrix, leaving nano-sized pores in the graphite particles after volatilization. These pores provide convenient channels for the transmission of lithium ions, reduce the resistance of lithium ions to embedding and embedding between graphite layers, and reduce the impedance of artificial graphite negative electrode materials.
[0051] The present invention also provides a fast-charging artificial graphite negative electrode material prepared by the above method.
[0052] According to an embodiment of the present invention, the fast-charging artificial graphite negative electrode material has a secondary particle structure.
[0053] According to an embodiment of the present invention, the secondary particle structure is composed of small particle size (D 50 The single graphite particles (5-8 μm) are bonded together, wherein the single graphite particles have nano-sized pores in the direction perpendicular to the graphite plane layer (C axis). The nano-sized pores are formed by heat treatment of high-sulfur coke.
[0054] According to an embodiment of the present invention, the small particle size (D 50 The single-grain graphite with a diameter of 5-8 μm is formed by graphitization of desulfurized coke powder.
[0055] According to an embodiment of the present invention, in the secondary particle structure, the graphite structure between adjacent single graphite particles has nanometer-sized pores, and the nanometer-sized pores are formed by graphitization of metal oxides.
[0056] According to an embodiment of the present invention, the median particle size D of the fast-charging artificial graphite negative electrode material is 50 10-15μm.
[0057] The present invention also provides the use of the above-mentioned fast-charging artificial graphite negative electrode material, which is used in lithium-ion batteries, preferably used to prepare the negative electrode of lithium-ion batteries.
[0058] The present invention also provides a negative electrode for a lithium-ion battery, wherein the negative electrode comprises the above-mentioned fast-charging artificial graphite negative electrode material.
[0059] Beneficial effects of the present invention:
[0060] The present invention selects high-sulfur coke with a sulfur content of 3-8wt% as raw material, and selects a staged heating heat treatment process for desulfurization treatment, thereby synergistically removing harmful sulfur in the high-sulfur coke and realizing C-axis pore formation of graphite. By controlling the volatilization rate of sulfur, the collapse of the high-sulfur coke structure is avoided. At the same time, the reconstructed porous desulfurized coke can ensure the order of the C-axis pore-forming graphite, which is beneficial to the pore structure and active sites for lithium ion embedding, de-embedding and transmission, thereby effectively improving the rate performance of the prepared fast-charging artificial graphite negative electrode material.
[0061] Furthermore, the present invention also uses a metal oxide (such as nano-sized Al 2 O 3 、SiO 2 or TiO 2 ) is used as a binder for the secondary granulation of small-particle desulfurized coke powder. The volatilization of metal oxides during the graphitization process will form nano-sized pores between single-particle graphite (formed after graphitization of small-particle desulfurized coke powder), which provides a convenient channel for the transmission of lithium ions to graphite, reduces the resistance of lithium ions to embed and embed in the graphite layers, reduces the impedance of the artificial graphite negative electrode material, and further improves the fast charging performance of the artificial graphite negative electrode material. DETAILED DESCRIPTION
[0062] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0063] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0064] Example 1
[0065] (1) placing high-sulfur coke with a sulfur content of 3 wt% into a high-temperature furnace, heating it to 350°C at a rate of 10°C / min under nitrogen protection, and keeping it at that temperature for 3 hours; then heating it to 1000°C at a rate of 5°C / min, and keeping it at that temperature for 2 hours; finally heating it to 1800°C at a rate of 1°C / min, and keeping it at that temperature for 6 hours, to obtain desulfurized coke;
[0066] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 5 μm);
[0067] (3) 100 g of asphalt (softening point 70 °C) was placed in a reactor and heated to 140 °C. 6 g of AlCl 3 Gradually add it into the molten asphalt and react for 1 hour, then seal the reactor and introduce argon, continue to heat to 350℃ and continue to react for 4 hours to obtain modified asphalt (softening point 120℃);
[0068] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 500° C. for 5 hours, and cooled to room temperature; then carbonized at 850° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 10 μm);
[0069] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 2950° C. for 12 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0070] Example 2
[0071] (1) High-sulfur coke with a sulfur content of 4wt% is placed in a high-temperature furnace, and the temperature is raised to 360°C at 15°C / min under nitrogen protection, and kept at this temperature for 3 hours; then the temperature is raised to 1000°C at 6°C / min, and kept at this temperature for 1-3 hours; finally, the temperature is raised to 1750°C at 2°C / min, and kept at this temperature for 6 hours.
[0072] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 7 μm);
[0073] (3) 100 g of asphalt (softening point 75 °C) was placed in a reactor and heated to 120 °C. Under stirring (500 r / min), 8 g of SiCl 4 Gradually add it into the molten asphalt and react for 1 hour, then seal the reactor and introduce argon, continue to heat to 380℃ and continue to react for 5 hours to obtain modified asphalt (softening point 110℃);
[0074] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 520° C. for 5 hours, and cooled to room temperature; then carbonized at 1000° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 13 μm);
[0075] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 3050° C. for 10 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0076] Example 3
[0077] (1) placing high-sulfur coke with a sulfur content of 5 wt% into a high-temperature furnace, heating it to 500°C at 20°C / min under nitrogen protection, and keeping it at that temperature for 1 hour; then heating it to 1200°C at 8°C / min, and keeping it at that temperature for 1 hour; finally heating it to 1850°C at 3°C / min, and keeping it at that temperature for 4 hours, to obtain desulfurized coke;
[0078] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 8 μm);
[0079] (3) 100 g of asphalt (softening point 68 °C) was placed in a reactor and heated to 125 °C. 10 g of TiCl 4 Gradually add it into the molten asphalt and react for 1 hour, then seal the reactor and introduce argon, continue to heat to 390℃ and continue to react for 3 hours to obtain modified asphalt (softening point 140℃);
[0080] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 650° C. for 3 hours, and cooled to room temperature; then carbonized at 900° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 15 μm);
[0081] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 3150° C. for 16 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0082] Comparative Example 1
[0083] (1) placing high-sulfur coke with a sulfur content of 3 wt% into a high-temperature furnace, heating it to 350°C at a rate of 10°C / min under nitrogen protection, and keeping it at that temperature for 3 hours; then heating it to 1000°C at a rate of 5°C / min, and keeping it at that temperature for 2 hours; finally heating it to 1800°C at a rate of 1°C / min, and keeping it at that temperature for 6 hours, to obtain desulfurized coke;
[0084] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 5 μm);
[0085] (3) 100 g of asphalt (softening point 70°C) was placed in a reactor and heated to 140°C for 1 hour. Then, the reactor was sealed and argon was introduced. The temperature was further raised to 390°C and the reaction was continued for 6 hours to obtain modified asphalt (softening point 120°C).
[0086] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 500° C. for 5 hours, and cooled to room temperature; then carbonized at 850° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 10 μm);
[0087] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 2950° C. for 12 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0088] Comparative Example 2
[0089] (1) placing high-sulfur coke with a sulfur content of 3 wt% into a high-temperature furnace, heating it to 1800°C at a rate of 10°C / min under nitrogen protection, and keeping the temperature for 6 hours to obtain desulfurized coke;
[0090] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 5 μm);
[0091] (3) 100 g of asphalt (softening point 70 °C) was placed in a reactor and heated to 140 °C. 6 g of AlCl 3 Gradually add it into the molten asphalt and react for 1 hour, then seal the reactor and introduce argon, continue to heat to 350℃ and continue to react for 4 hours to obtain modified asphalt (softening point 120℃);
[0092] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 500° C. for 5 hours, and cooled to room temperature; then carbonized at 850° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 10 μm);
[0093] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 2950° C. for 12 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0094] Comparative Example 3
[0095] (1) placing high-sulfur coke with a sulfur content of 10 wt% into a high-temperature furnace, heating it to 350°C at 10°C / min under nitrogen protection, and keeping it at that temperature for 3 hours; then heating it to 1000°C at 5°C / min, and keeping it at that temperature for 2 hours; finally heating it to 1800°C at 1°C / min, and keeping it at that temperature for 6 hours, to obtain desulfurized coke;
[0096] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 5 μm);
[0097] (3) 100 g of asphalt (softening point 70 °C) was placed in a reactor and heated to 140 °C. 6 g of AlCl 3 Gradually add it into the molten asphalt and react for 1 hour, then seal the reactor and introduce argon, continue to heat to 350℃ and continue to react for 4 hours to obtain modified asphalt (softening point 120℃);
[0098] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 500° C. for 5 hours, and cooled to room temperature; then carbonized at 850° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 10 μm);
[0099] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 2950° C. for 12 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0100] Comparative Example 4
[0101] (1) placing high-sulfur coke with a sulfur content of 3 wt% into a high-temperature furnace, heating it to 350°C at a rate of 10°C / min under nitrogen protection, and keeping it at that temperature for 3 hours; then heating it to 1000°C at a rate of 5°C / min, and keeping it at that temperature for 2 hours; finally heating it to 1800°C at a rate of 1°C / min, and keeping it at that temperature for 6 hours, to obtain desulfurized coke;
[0102] (2) crushing the desulfurized coke obtained in step (1) in an impact mill, and then shaping and classifying the crushed desulfurized coke to obtain desulfurized coke powder (with a median particle size of 5 μm);
[0103] (3) 100 g of asphalt (softening point 70 °C) was placed in a reactor and heated to 140 °C. 6 g of Al 2 O 3 (median particle size of 20 nm) was gradually added to the molten asphalt to react for 1 hour, and then the reactor was sealed and argon was introduced, and the temperature was continued to rise to 350°C and the reaction was continued for 4 hours to obtain modified asphalt (softening point 120°C);
[0104] (4) 100 g of the desulfurized coke powder of step (2) and 10 g of the modified asphalt of step (3) were mixed evenly, and then stirred in a granulation kettle at 500° C. for 5 hours, and cooled to room temperature; then carbonized at 850° C. for 5 hours under nitrogen, and cooled to room temperature to obtain secondary coke particles (median particle size of 10 μm);
[0105] (5) The secondary coke particles of step (4) are graphitized at a high temperature of 2950° C. for 12 hours, and then cooled to room temperature to obtain the fast-charging artificial graphite negative electrode material.
[0106] Test Example 1
[0107] Electrochemical performance test
[0108] Semi-electric test method: The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-4: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) were mixed evenly and applied on copper foil. The coated electrode was placed in a vacuum drying oven at 120°C and dried for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon gas. The electrolyte was 1M-LiPF 6 +EC:DEC:DMC (volume ratio of 1:1:1), metal lithium sheet as the counter electrode, simulated battery test in 5V, 10mA Xinwei battery test cabinet, the charge and discharge voltage is 0.01-1.5V, the charge and discharge rate is 1C, the first discharge capacity and first coulomb efficiency obtained from the test are shown in Table 1.
[0109] Full battery test method: The graphite materials prepared in Examples 1-3 and Comparative Examples 1-4 were used as negative electrodes, lithium cobalt oxide was used as positive electrodes, and 1M-LiPF 6 +EC:DEC:DMC (volume ratio 1:1:1) solution was used as the electrolyte to assemble a full battery, which was charged and discharged at room temperature at a rate of 6C with a voltage range of 3.0-4.2V. The cycle performance obtained from the test is shown in Table 1.
[0110] Table 1 Electrochemical performance test results
[0111]
[0112] It can be seen from Table 1 that the artificial graphite negative electrode material prepared by the present invention has good rate performance, while the artificial graphite negative electrode materials of Comparative Examples 1-4 cannot obtain good rate performance, which is mainly due to:
[0113] The asphalt used in the secondary granulation of the artificial graphite negative electrode material in Comparative Example 1 does not contain nano-sized metal oxides, which results in a denser graphite structure converted from the asphalt that bonds single-particle graphite during the graphitization process, reducing the diffusion rate of Li+ to the surface of graphite (C-axis pore formation), and therefore can only improve its rate performance to a certain extent.
[0114] The high-sulfur coke used in Comparative Example 2 has a fast volatilization rate of sulfur during desulfurization heat treatment, and cannot effectively form C-axis pores on the graphite surface, which is not conducive to the acquisition of pore structure and active sites for lithium ion embedding, de-embedding and transmission; in addition, although there are nanopores between single graphite particles in the artificial graphite negative electrode material, these nanopores can only provide convenient channels for the transmission of lithium ions to graphite, but cannot form pores on the C-axis of the artificial graphite negative electrode material; this leads to slow diffusion kinetics of lithium ion embedding and de-embedding between graphite layers, and thus the rate performance of the artificial graphite negative electrode material is very low.
[0115] The sulfur content in the high-sulfur coke used in Comparative Example 3 is too high. Although the C-axis of the prepared artificial graphite negative electrode material has holes, the volatilization of a large amount of sulfur causes the collapse of the petroleum coke structure, resulting in lower capacity, first coulombic efficiency and lower rate performance, making it difficult to apply to lithium-ion batteries.
[0116] In Comparative Example 4, nano-alumina is directly added to asphalt to prepare modified asphalt. During the addition process, nano-alumina will have obvious agglomeration problems, which makes it impossible to evenly distribute in the modified asphalt. This results in the inability to form nano-sized pores between single graphite particles during the graphitization process, reducing the diffusion rate of Li+ to the graphite (C-axis pore formation) surface, and therefore can only improve its rate performance to a certain extent.
[0117] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a fast-charging artificial graphite negative electrode material, the method comprising the following steps: (1) heat treating high-sulfur coke to prepare desulfurized coke; (2) crushing, shaping and classifying the desulfurized coke obtained in step (1) to obtain desulfurized coke powder; (3) mixing asphalt and metal chloride, reacting, and preparing modified asphalt; (4) mixing the desulfurized coke powder of step (2) and the modified asphalt of step (3) to react; (5) carbonizing the reaction product of step (4) to prepare secondary coke particles; (6) graphitizing the secondary coke particles of step (5) to prepare the fast-charging artificial graphite negative electrode material; Wherein, in step (1), the heat treatment adopts a staged heating process, which specifically includes the following steps: First, heat up to 300-500°C at a heating rate of 10-20°C / min and keep warm for 1-3 hours; then heat up to 800-1200°C at a heating rate of 5-10°C / min and keep warm for 1-3 hours; finally, heat up to 1700-2000°C at a heating rate of 1-5°C / min and keep warm for 1-6 hours.
2. The preparation method according to claim 1, wherein In step (1), the sulfur content in the high-sulfur coke is 3-8wt%; And / or, in step (1), the heat treatment is carried out under a nitrogen protective atmosphere; And / or, in step (1), the sulfur content in the desulfurized coke is less than 100 ppm; And / or, in step (2), the median particle size D of the desulfurized coke powder is 50 5-8μm.
3. The preparation method according to claim 1 or 2, wherein In step (3), the softening point of the asphalt is 65-75°C; and / or, in step (3), the water content in the asphalt is 2-3 wt%; And / or, in step (3), the metal chloride is selected from AlCl3, SiCl4 or TiCl4; And / or, in step (3), the mass ratio of the metal chloride to the asphalt is (5-15):100; And / or, in step (3), the softening point of the modified asphalt is 100-150°C.
4. The preparation method according to any one of claims 1 to 3, wherein: Step (3) specifically includes the following steps: Put asphalt into a reactor and heat it to 120-160°C, add metal chloride to the molten asphalt under stirring, react for 0.5-1 hour, then introduce argon into the reactor, continue heating to 330-390°C under argon protection, keep warm for 2-6 hours, and prepare modified asphalt.
5. The preparation method according to any one of claims 1 to 4, wherein: In step (4), the mass ratio of the modified asphalt to the desulfurized coke powder is (8-15):100; And / or, in step (4), the reaction temperature is 450-650° C.; the reaction time is 3-12 hours.
6. The preparation method according to any one of claims 1 to 5, wherein: In step (5), the temperature of the carbonization treatment is 800-1000° C.; the time of the carbonization treatment is 3-12 hours; And / or, in step (5), the carbonization treatment is carried out under a nitrogen atmosphere; And / or, in step (6), the temperature of the graphitization treatment is 2850-3200° C.; the time of the graphitization treatment is 8-24 hours.
7. A fast-charging artificial graphite negative electrode material prepared by the method according to any one of claims 1 to 6.
8. The fast-charging artificial graphite negative electrode material according to claim 7, wherein: The fast-charging artificial graphite negative electrode material has a secondary particle structure. Preferably, the secondary particle structure is formed by bonding together single graphite particles of small particle size, wherein the single graphite particles have nano-sized pores in a direction perpendicular to the graphite plane layer. Preferably, in the secondary particle structure, the graphite structure between adjacent single graphite particles has nano-sized pores.
9. Use of the fast-charging artificial graphite negative electrode material according to claim 7 or 8, which is used in lithium-ion batteries.
10. A negative electrode for a lithium-ion battery, the negative electrode comprising the fast-charging artificial graphite negative electrode material according to claim 7 or 8.
Citation Information
Patent Citations
Stepwise desulfurization of fluid coke with steam and hydrogen
CA579100A
Method for desulfurizing petroleum coke
CN101760279A
Asphalt-based nanoporous carbon material, negative material thereof, and lithium ion battery
CN104300150A
Single-particle negative electrode material produced from medium sulfur coke
CN115872398A
Artificial graphite negative electrode material and preparation method and application thereof
CN116654922A